Beyond retributive justice: listening to environmental victims’ demands in Brazil - Budó, Marília de Nardin (Green crime in the global south, 2023)
Studies in green criminology have confirmed how important it is for criminology to turn its focus to environmental risks, harms, and massive tragedies caused by human activity. Specifically, Southern green criminology has shown how the coloniality of knowledge limits the imagination when comprehending and analysing environmental harm, the victims, and the possibilities of justice. Considering that the criticism of retributive justice is part of a Southern green criminology perspective, this chapter seeks to discuss alternatives to the criminal justice system to deal with environmental conflicts involving corporations and local communities in Brazil. First, the authors address the debate on massive environmental victimisation, through a review of empirical studies. Second, they address some of the challenging specificities of environmental harm and crime, highlighting the collective character of the victimisation process; the unbalanced power relationship between victims and perpetrators; the ties between the state and corporations; and the demands for justice, memory, and truth, not only to repair the past, but to prevent harm in the future. Finally, they approach the question of how restorative justice could contribute to dealing with environmental conflicts caused by economic activities in the global South.